Impact of outsourcing and economic development on productivity and technical efficiency of airlines / Muhammad Asraf Abdullah - Muhammad Asraf, Abdullah (2017)
The principal objectives of this study are twofold. Firstly, it attempts to evaluate the technical efficiency and productivity growth of 56 global airlines that operate in two types of business models namely full cost and low cost carriers. Secondly, this study aims to investigate the influence of outsourcing extent and economic development on the performance of airlines from the perspectives of technical efficiency and productivity growth. The study assesses the technical efficiency of full cost and low cost carriers by applying the concept of metafrontier technical efficiency which is introduced by O’ Donnell et al. (2008). Next, the evaluation of productivity change employs the metafrontier concept of Malmquist Productivity Index (MPI) as suggested by Oh and Lee (2010). Finally, the influence of outsourcing and economic development on the technical efficiency and productivity growth are estimated using the One Step System, Generalized Method of Moments estimator (GMM). The findings from the technical efficiency analysis indicate that full cost carrier is narrowing the technical efficiency gap between the group frontier and the metafrontier technologies as depicted by the high scores of the technology gap ratio throughout the period of study from 2002 to 2011. This implies that full cost carrier is moving closer towards the world technology frontier. As such, this suggests that the full cost carrier forms the world technology frontier. On the other hand, the findings from the productivity analysis demonstrate that the low cost carriers gained the highest change in productivity growth of 3.7 percent throughout the period examined from 2002/2003 to 2010/2011, whilst full cost carriers recorded a marginal fall of 0.5 percent in the productivity growth. The main contributing factors to the decent productivity growth of low cost carriers are due to two reasons. Firstly, the capability of low cost carriers to efficiently squeeze its available inputs in order to maximize the production of output. In essence, the result implies that low cost carriers are good at catching up. Secondly, the positive change in technology gap ratio suggests that low cost carriers has the capacity to speed up the technological development as shown by a moderate growth rate of 0.7 percent annually in the technology gap ratio. The findings from the GMM estimators revealed an indirect yet positive relationship between outsourcing and performance indicators which are technical efficiency and productivity growth. The results from the analysis exhibit positive influences of outsourcing on technical efficiency and productivity growth in the context of small-scale airlines. In essence, these findings suggest a significant role of outsourcing in influencing the technical efficiency and productivity growth in small-scale airlines. Similarly, economic development level shows a positive association with the productivity growth of airlines but negative for technical efficiency. These findings further indicate that economic development improves the productivity of airlines only in the presence of high quality of governance.